Languages and compilers for parallel computing : 28th International Workshop, LCPC 2015, Raleigh, NC, USA, September 9-11, 2015. Revised selected papers /: 28th International Workshop, LCPC 2015, Raleigh, NC, USA, September 9-11, 2015. Revised selected papers. (2016) - Unknown
No abstract available